Struggling with destiny in Karimpur, 1925-1984 - Wadley, Susan Snow, 1943- (Berkeley : University of California Press, 1994)
Susan Wadley first visited Karimpur--the village "behind mud walls" made famous by William and Charlotte Wiser--as a graduate student in 1967. She returned often, adding hears of changes in agriculture, labor relations, education, and the family. But Karimpur's residents do not speak with one voice in describing the ways their lives have changed--viewpoints vary considerably depending on the speaker's gender, economic status, and caste. Using cultural documents such as songs and stories, as well as data on household budgets and farming practices, Wadley examines what it means to be poor or rich, female or male. She demonstrates that the forms of subordination prescribed for women are paralleled by those prescribed for lower castes
1. "Tell Them to Listen with Their Ears Open" Increasing Disorder. Making Their Own Destiny. Karimpur and Its Environs, 1925-1984. Four Lives. Raghunath, a Cultivator. Santoshi, the Midwife. Saroj, a Brahman Widow. Mohan, an Elderly Brahman -- 2. "There Should Be Control" Knowledge, Control, and Gender. "One Straw from a Broom Cannot Sweep" Shankar, the Village Headman, and Sufhir, a Poor Brahman -- 3. "Power Comes through Money" Brahman by Birth. Brahmans as Patrons. Power in Karimpur. Gaining and Maintaining Honor. Brahman Lifestyles. Sheila, the Washerwoman -- 4. "Poverty Is Written in My Destiny" Living One's Destiny. Sorrow. Being Poor. Escaping Poverty. Jiji and Kamla, Two Widows -- 5. "The Domination of Indira" The Increasing Intrusion of the State into Agriculture. Rural Development Schemes. Health Care and the State. Attitudes toward Education. The Landlord's Loss of Dominance. Sunita, the Shepherd's Wife, and Saroj Revisited -- 6. "Now Love Is Totally Lost."
Includes bibliographical references (pages 277-290) and index.
Print version record.
In English.
eBooks on EBSCOhost
Keywords: Ethnology -- India -- Mainpuri (District); Villages -- India -- Mainpuri (District); Families -- India -- Mainpuri (District); Social change -- India -- Mainpuri (District); Mainpuri (India : District) -- Social conditions; Mainpuri (India : District) -- Rural conditions; Villages; Ethnologie -- Inde -- Mainpuri (District); Villages -- Inde -- Mainpuri (District); Familles -- Inde -- Mainpuri (District); Villages; villages; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; SOCIAL SCIENCE / Anthropology / Cultural & Social; Ethnology; Families; Rural conditions; Social change; Social conditions; Villages; India -- Mainpuri (District); Dorf; Sozialer Wandel; Uttar Pradesh; Karimpur; Agrarische maatschappij; Sociaal-economische verandering; Villages -- Inde -- Mainpuri (district); Changement social -- Inde -- Mainpuri (district); Famille -- Inde -- Mainpuri (district); Mainpuri (Inde ; district) -- Conditions sociales; Social conditions -- History; Uttar Pradesh (India)